CINEMA SPACES: AN IMAGINATIVE WORLD OF THE CULTURAL LANDSCAPE. REVIEW OF THE 6TH INTERNATIONAL SCIENTIFIC CONFERENCE “GEOGRAPHY OF ART” / ПРОСТРАНСТВА КИНО: ОБРАЗНЫЙ МИР КУЛЬТУРНОГО ЛАНДШАФТА. ОБЗОР VI МЕЖДУНАРОДНОЙ НАУЧНОЙ КОНФЕРЕНЦИИ «ГЕОГРАФИЯ ИСКУССТВА» - LAVRENOVA OLGA A. / ЛАВРЕНОВА О.А. (Наука телевидения, 2020)
The international scientific conference “Geography of Art” is devoted to the development of a wide problematic field of interaction between art and geographic space. It traditionally considers not only spacing of artifacts and monuments over the earth’s surface, but also specific features related to the reflection of geographical space in art and creation of fantasy worlds in which the dependence on consistent patterns of the real world formation can easily be traced. The conference has been held since 2009; it was initiated by the geographer Yu.A. Vedenin and carried forward by the philosopher and culture specialist O.A. Lavrenova. In recent years, organizers of this representative forum are the Institute of Scientific Information for Social Sciences of the Russian Academy of Sciences, the Russian Academy of Arts, Film and Television School (GITR), the Russian State University for the Humanities. In 2020, for the first time the conference was held online. As always, there was discussed the role of territorial factors in formation of art schools and individual works, as well as a creative perception of the cultural landscape, the place of art in the formation of the territory image. An important topic was a concept of space in art works, the possibilities of comprehending, transforming, “reformatting” the space by different art types including screen art, creating in this way the “increment of meaning” of places and regions. Within the framework of this conference there were discussed historical and cultural features of the national and world cinema, which capture real spaces and create their own modifications. Participants touched upon the topic of traveling in the cinema, virtual representations of cultural landscapes using digital narratives and, accordingly, the possibilities and specific features of the virtual travel. The issue of studying urban spaces by means of cinema was considered in a wide semantic variety—from buffoonery to marginality. A city appears as a universal scenery for a performance while real street loci with their inhabitants become heroes of modern visual media. A separate topic was the discussion of constructed spaces of Korean TV series and their adaptation in Russian culture as a tangible result of the process of intercultural communication. All the above mentioned studies represented by conference participants actually complement each other in terms of understanding the figurative component of the cultural landscape.